2022
DOI: 10.1155/2022/7455494
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin-d Attenuates Hashimoto’s Thyroiditis by Regulating Macrophage Polarization

Abstract: Objective. Hashimoto’s thyroiditis (HT) is one of the most common clinical autoimmune diseases. Recent studies have found that HT pathogenesis is associated with macrophage polarization. Saikosaponin-d (SSd) is an active component in the Chinese medicine Bupleurum, which has anti-inflammatory and immunomodulatory effects. The purpose of this study was to verify the therapeutic effect of SSd on HT and to investigate the regulatory effect of SSd on macrophage polarization in HT. Methods. Network pharmacology ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A study using single-cell RNA sequencing found that immune-dysregulated cells interact and activate relevant immune pathways and further aggravate the immune response in patients 38 . A decrease in Treg cells and an increase in Th17 cells in the peripheral blood of patients with HT have been previously reported 39 , 40 . Evidence shows that an imbalance in the Th17/Treg ratio is a prognostic factor for thyroid gland damage 41 .…”
Section: Discussionmentioning
confidence: 65%
“…A study using single-cell RNA sequencing found that immune-dysregulated cells interact and activate relevant immune pathways and further aggravate the immune response in patients 38 . A decrease in Treg cells and an increase in Th17 cells in the peripheral blood of patients with HT have been previously reported 39 , 40 . Evidence shows that an imbalance in the Th17/Treg ratio is a prognostic factor for thyroid gland damage 41 .…”
Section: Discussionmentioning
confidence: 65%
“…A study using single-cell RNA sequencing found that immunedysregulated cells interact and activate relevant immune pathways and further aggravate the immune response in patients 37 . A decrease in Treg cells and an increase in Th17 cells in the peripheral blood of patients with HT have been previously reported 38,39 . Evidence shows that an imbalance in the Th17/Treg ratio is a prognostic factor for thyroid gland damage 40 .…”
Section: Discussionmentioning
confidence: 66%
“…The top five scoring nodes based on degree were ALB, MMP9, TNF, HIF1A, PTGS2, IL1B, STAT3, PPARG, PTEN, BCL2, ICAM1, MAPK1, and RELA (Table 2). A review of previous studies and literature research revealed that the targets are closely related to macrophage polarization [26,27] .…”
Section: Resultsmentioning
confidence: 99%
“…MMP9, PTGS2, STAT3, and PPARG may also be involved in the regulation of macrophage polarization and inflammation by PRA. For example, overexpression of MMP9 can promote M1 phenotype transformation in LPS-induced murine pulmonary macrophages, whereas inhibition of MMP9 expression can promote M2 phenotype transformation [26,27] . The KEGG pathway enrichment analysis revealed various pathways related to macrophage polarization, including the TNF signaling pathway, mitogen-activated protein kinase (MAPK) signaling pathway, Toll-like receptor signaling pathway, NF-κB signaling pathway, and phosphoinositide 3-kinase-Akt (PI3K/Akt) signaling pathway.…”
Section: Discussionmentioning
confidence: 99%